2008
DOI: 10.1007/978-3-540-69905-7_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Image Restoration Methods for Bioluminescence Imaging

Abstract: Abstract. Bioluminescence imaging is a recent modality to visualize biological effects more especially for small animals. However the acquired images are degraded by diffusion and absorption phenomena from the tissue and by the acquisition system itself. In this paper, we use restoration methods to enhance the quality of bioluminescence images. We propose a model for image formation and an experimental determination of the PSF (Point Spread Function). Several methods of restoration are compared on test images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…We showed that the restoration had no significant impact on the quantitation ( n = 15 measurements) according to the results obtained with synthetic images. 10…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed that the restoration had no significant impact on the quantitation ( n = 15 measurements) according to the results obtained with synthetic images. 10…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of previous results, 10 the blind deconvolution method was used to restore the bioluminescent images. With this method, accurate a priori knowledge of the PSF is not necessary but allows the algorithm to converge more quickly.…”
Section: Restoration Of In Vivo Bioluminescent Imagesmentioning
confidence: 99%
See 2 more Smart Citations